Glacial Lakes of Mongolia - Michael Walther; Ulrich Kamp; Nyam-Osor Nandintsetseg; Avirmed Dashtseren; Khurelbaatar Temujin (Geographies, 2024)
The over 2200 lakes of Mongolia are generally poorly studied, particularly the glacial lakes. This overview study presents a classification of the glacial lakes based on tectonic-geological and geomorphological dynamics. Selected representative lakes are described using results from fieldwork and satellite image analysis, including bathymetry, paleoshorelines, and recent lake-level fluctuations between 1987 and 2020. Generally, lake levels dropped from the early Holocene until recently, with the onset of the climate change-driven glacier recession that has resulted in lake-level rises and area expansion in almost all moraine-dammed, tongue-basin, and ice-contact lakes. In contrast, endorheic lakes have mainly been shrinking for the past forty years because of an increase in air temperature and evaporation rates and the effects of an intensifying water use within the catchment for irrigation, mining, and hydroelectric energy production in the form of dams. The creation of a lake monitoring system based on an in-depth inventory is recommended.